Free-form surface machining error compensation applying 3D CAD machining pattern model. (May 2015) - Poniatowska, Malgorzata
Abstract: The article presents a methodology for compensating for systematic influences of computer numerical control (CNC) machining processes on free-form surfaces. The proposed procedure is performed off-line by introducing corrections compensating for these influences to machining programs. The effect of systematic influences of machining are deterministic deviations of surfaces. CAD models of these deviations, averaged for a number of surfaces machined under repeatable conditions, represent a machining pattern model (MPM) which serves as the basis for performing compensation. The basis for developing such models is surface deviations determined during coordinate measurements carried out along a regular grid of points. For estimating surface MPMs, a methodology is proposed in which regression analysis, spatial statistics methods, an iterative procedure, and NURBS modeling are applied. An MPM with the opposite sign was used for compensating systematic influences of the ball-end milling process by modifying the nominal geometry data and correcting the machining program. The results of machining error compensation carried out on the basis of a previously developed MPM were compared to the results of compensation performed on the basis of raw measurement data as well as to the results these after compensation on the basis of a model of deterministic deviations for the surface under study. Highlights: I propose the method for compensating for systematic errors of free-form surfaces. The basis for performing compensation is machining pattern model (MPM). MPM represents the most probable shape of errors in the machining process. MPM is available in a very convenient CAD format. The application of the MPM provides a high effectiveness of error compensation.